A WIDEBAND BEAR-SHAPED COMPACT SIZE IMPLANTABLE ANTENNA FOR IN-BODY COMMUNICATIONS - Ahmad, Sarosh; Manzoor, Bilal; Paracha, Kashif Nisar; Haider, Sajjad; Liaqat, Maryam; Al Gburi, Ahmed Jamal Abdullah; Ghaffar, Adnan; Alibakhshikenari, Mohammad; Dalarsson, Mariana (MDPI, 2022)
Biomedical implantable antennas play a vital role in medical telemetry applications. These types of biomedical implantable devices are very helpful in improving and monitoring patients’ living situations on a daily basis. In the present paper, a miniaturized footprint, thin-profile bear-shaped in-body antenna operational at 915 MHz in the industrial, scientific, and medical (ISM) band is proposed. The design is a straightforward bear-shaped truncated patch excited by a 50-Ω coaxial probe. The radiator is made up of two circular slots and one rectangular slot at the feet of the patch, and the ground plane is sotted to achieve a broadsided directional radiation pattern, imprinted on a Duroid RT5880 roger substrate with a typical 0.254-mm thickness ( er = 2.2, tan δ = 0.0009). The stated antenna has a complete size of 7 mm × 7 mm × 0.254 mm and, in terms of guided wavelength, of 0.027λg × 0.027λg × 0.0011λg. When operating inside skin tissues, the antenna covers a measured bandwidth from 0.86 GHz to 1.08 GHz (220 MHz). The simulations and experimental outcomes of the stated design are in proper contract. The obtained results show that the calculated specific absorption rate (SAR) values inside skin of over 1 g of mass tissue is 8.22 W/kg. The stated SAR values are lower than the limitations of the federal communications commission (FCC). Thus, the proposed miniaturized antenna is an ultimate applicant for in-body communications.